The methods of numerical mechanics for the improvement of machine-tools - Szilágyi, Attila; Kiss, Dániel (Design of Machines and Structures, 2020)
This paper gives a brief summary on the mechanical and thermal applicability of the finite element method (FEM) from the field of designing procedure of machine tools. The solutions of certain problems, as examples, are also demonstrated. First the summary of such phenomena is performed, where the application of numerical methods is inevitable. Through the brief summary of the general problem of elasticity, the justification of the numerical methods is demonstrated. Finally, examples are set to demonstrate the applicability of the numerical methods and the achieved results, which demonstrate the efficiency of the FEM applied for the development of machine tools. Among several numerical methods the FEM is focused on in this paper.